Dynamic Properties of the Railway Track - Moravcik, Milan (Communications - Scientific letters of the University of Zilina, 2007)
The paper is focused on different aspects of track dynamics and train-track interaction. The dynamic modeling of railway track response and of the interaction of vehicle and track at low and mid frequencies, that are significant for the track deterioration, is presented. Dynamic properties of the track structure as a whole is described and evaluated including the dynamics of compound train-track system. The dynamic amplification resulting from the simulated passage of the locomotive of the type E 499.0 (85t) is presented.